Miles’s Trauma in Collen Hoover’s Ugly Love - Pancarani, Anindya Lintang; Wahyono, Danu (Sintuwu Maroso Journal of English Teaching, 2024)
The title of this study is Miles’s Trauma in Colleen Hoover’s Ugly Love. The objective of this research is to examine the trauma suffered by Miles Archer as the main character. It uses qualitative method, and the research design is using psychological approach as a literary approach. The study aims to explore and find the cause of the trauma, and their effects on the character, and how the character solves the trauma. The results shows that the cause of his trauma is relate to the abandonment by his first love Rachel due to the car crash that result the death of their newborn baby. He is not just devastated by Rachel’s departure, but also the death of his son which make him lose person he loves the most. After Rachel left him, he promises himself not to fall in love with anyone again. The effects of his trauma also reveal that he faces difficulty and problems with relationships. The way Miles solves his trauma is by facing and accepting his fear and learning how to manage his feelings in order to heal.